Student and Research and Teaching Staff Engagement as an Indicator of Corporate Culture Assessment and a Tool for University’s Personnel Reserve Formation - V. D. Kolychev; N. A. Budanov (Высшее образование в России)
The article analyzes the results of measuring the parameters of the engagement of students and research and teaching staff of the university. Based on the experience of the leading consulting companies, MEPhI has developed a technology for assessing the engagement parameters used to measure the level of emotional state of personnel. A special feature of the developed methods for assessing the engagement parameters is the possibility of practical application of the results of analytical research for subsequent management decision-making, as well as the use of the proposed approach by the organizations of higher education. The assessment of the parameters of engagement is focused on solving the problems of increasing the competitiveness of the university by improving the key areas affecting the development of corporate culture: performance management, the possibility of personnel professional development and career growth, the creation of adaptive mechanisms of remuneration and recognition, the development of effective communication methods, improvement of decision-making in the field of infrastructure support, the development of a personnel reserve and mechanisms for adaptation and attraction of young employees. The developed methods for assessing the parameters of engagement incorporate the best practices of domestic and foreign high-tech companies, including the experience of Rosatom State Corporation. The results of the engagement parameters assessment are considered as tools for carrying out work to raise the University performance due to improving the University corporate culture and forming high-potential personnel reserve.